The homology gene BtDnmt1 is Essential for Temperature Tolerance in Invasive Bemisia tabaci Mediterranean Cryptic Species - Tian-Mei Dai (Nature Portfolio, 2017)
Abstract The Bemisia tabaci Mediterranean (MED) cryptic species has been rapidly invading most parts of the world owing to its strong ecological adaptability, particularly its strong resistance to temperature stress. Epigenetic mechanisms play important roles in mediating ecological plasticity. In particular, DNA methylation has been the focus of attempts to understand the mechanism of phenotypic plasticity. The relationship between temperature and DNA methylation and how it affects the adaptability of invasive insects remain unknown. To investigate the temperature resistance role of DNA methyltransferase 1 (Dnmt1) in MED, we cloned and sequenced BtDnmt1 homology and identified its functions under various temperature conditions. The full-length cDNA of MED BtDnmt1 homology was 5,958 bp and has a 4,287 bp open reading frame that encodes a 1,428-amino-acid protein. BtDnmt1 mRNA expression levels were significantly down-regulated after feeding with dsRNA. Furthermore, after feeding with dsBtDnmt1, the MED adults exhibited significantly higher mortality under temperature stress conditions than the controls, suggesting that MED BtDnmt1 homology plays an essential role in the temperature tolerance capacity of MED. Our data improve our understanding of the temperature resistance and temperature adaptability mechanisms that have allowed the successful invasion and colonization of various environments by this alien species.